EFFECTIVENESS OF HEALTH EDUCATION ON FOOTWEAR SELECTION IN REDUCING FOOT ULCER INCIDENCE AMONG PATIENTS WITH TYPE 2 DIABETES MELLITUS - Rizki Hidayat; Naziyah Naziyah; Masdiana Masdiana (BRIN - Badan Riset dan Inovasi Nasional, 2026)
The incidence of diabetes mellitus in Indonesia is 10.8%. DM is a disease caused by the body's inability to produce insulin, which can lead to complications, one of the most common being foot ulcers. If foot conditions are not properly managed, they will worsen, leading to amputation. Prevention of foot ulcer. nvolves providing education on choosing footwear to reduce the incidence of foot injuries. This study aimed to determine the effect of footwear selection education on the incidence of foot ulcers among patients with type 2 diabetes mellitus.This research method a quasi-experimental design with a single intervention group. The sample used was 30 respondents, with the research instrument being the Inlow's 60-second diabetic foot screen observation sheet. This study was conducted by collecting pre-test data using the observation sheet on type 2 diabetes mellitus patients participating in Prolanis (Program Pengelolaan Penyakit Kronis), followed by education on footwear selection, evaluation, and post-test data collection over a month, with data processing using the Wilcoxon test.The results showed a decrease in the incidence of foot ulcers followinf the footwear selection education intervention. Statitical analysis indicated a significant effect of footwear selection education on reducing foot ulcer incidence among patients with type 2 diabetes mellitus (p<0.05). Education on footwear selection influences footwear choices among type 2 diabetes mellitus patients at the Pasar Minggu Community Health Centre. Type 2 diabetes mellitus patients are expected to implement the footwear selection provided not only for those undergoing treatment at the community health centre and prolanis but also at other healthcare facilities.